Association between chili pepper consumption and risk of gastrointestinal-tract cancers: A meta-analysis - Chen, Changchang; Zhang, Man; Zheng, Xutong; Lang, Hongjuan (Frontiers in Nutrition, 2022)
Background Stimulating food is emerging as an important modifiable factor in the development of gastrointestinal (GI) tract cancers, but the association between chili pepper consumption and the risk of GI cancers is unclear. We aimed to evaluate the direction and magnitude of the association between chili pepper consumption and the risk of GI cancers. Methods A literature search was performed in PubMed, Embase, and Web of Science databases from inception to 22 December 2021. Observational studies reporting the association between chili pepper consumption and the risk of gastric cancer (GC), esophageal cancer (EC), and/or colorectal cancer (CRC) in adults were eligible for inclusion. Data extraction and quality assessment were conducted independently by two reviewers for the included literature. Summary odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using a random-effects model. Subgroup analyses were also performed based on the cancer type, study design, region of the study, study quality, and adjustments. Results A total of 11,421 studies were screened, and 14 case-control studies were included involving 5009 GI cancers among 11,310 participants. The summary OR showed that high consumption of chili pepper was positively related to the risk of GI cancers (OR = 1.64; 95% CI: 1.00–2.70). A stronger positive relationship was observed between chili pepper consumption and EC risk (OR = 2.71; 95% CI: 1.54–4.75), but there was no statistically significant association between GC and CRC risk. In analyses stratified by geographical location, a positive association was found between chili pepper consumption and the risk of GI cancers in Asian studies (OR = 2.50; 95% CI: 1.23–5.08), African studies (OR = 1.62; 95% CI: 1.04–2.52), and North American studies (OR = 2.61; 95% CI: 1.34–5.08), but an inverse association was seen in South American studies (OR = 0.50; 95% CI: 0.29–0.87) and European studies (OR = 0.30; 95% CI: 0.15–0.61). Conclusion This meta-analysis suggests that chili pepper is a risk factor for certain GI cancers (e.g., EC). Geographical regions influence the risk of GI cancers, especially in Asian, African, and North American populations, which require more attention during dietary guidance. Systematic review registration [https://www.crd.york.ac.uk/PROSPERO/], identifier [CRD42022320670].